Keanekaragaman Jenis dan Kepadatan Burung Di Kawasan Taman Hutan Raya Lapak Jaru Kabupaten Gunung Mas Provinsi Kalimantan Tengah: Species Diversity and Density of Birds in Lapak Jaru Forest Park Area, Gunung Mas Regency, Central Kalimantan Province - Wulandary, Pratiwi Putri; Hidayat, Nisfiatul; Octavianus, Robby; Putir, Patricia Erosa; Yulianto, Santosa (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
This research aims to determine the diversity of species and population density of birds in the Lapak Jaru Forest Park (Tahura) Area. The method used is the Rapid Assessment method and a combination method between the Point Count method and Line Transect. Data analysis uses the Species Richness Index, Species Diversity Index, Evenness Index and Population Density. The research results showed that the number of bird species at the research location is 28 bird species with a total number of 238 individuals. The Species Richness Index obtained is 4,93, the Species Diversity Index is 2,96, and the Evenness Index is 0,89. The bird population density at the research location is 2,701.11 individuals/km2, and the five types of birds with the highest density are Cinenen Belukar (306,68 individuals/km2), Pentis Kalimantan (271,29 individuals/km2), Cucak Kelabu (235,9 individuals/km2), Asi Topi-Sisik (235,9 individuals/km2) and Jingjing Batu (176,93 individuals/km2)